The Evaluation of Industrial Based Learning Program to Improve Vocational Student Skills Competency - Marlina, Marlina (Faculty of Technological and Vocational Education-Universitas Pendidikan Indonesia, 2016)
This study was conducted based on the refinement or improvement of vocational secondary education to anticipate the future needs and challenges to be continuous alignment with the needs’ development of the business world of work, the development of science, technology, art and culture. The result of field observation syndicate that the majority of graduates of vocational schools (SMK) cannot be absorbed in the job, since the competent cites they have do not fulfill the demands of the working world yet. Problem formulation of this researches